Karakterisasi Enzim Komersial Siklodekstrin Glukanotransferase - Elidar Naiola; Nunuk Widhyastuti (Universitas Atma Jaya Yogyakarta, 2008)
The objective of this study is to investigate the characteristic of commercial enzyme Cyclodextrin Glucanotrasferase (CGTase) from Bacillus macerans. The CGTase was purified by dialysis, gel fitration and ion exchange chromatography. Study on Characterization of the enzyme showed that the hydrolytic activity of CGTase was 480 U/mg, the optimum tempetature and pH for enzyme reaction were 450C to 550C and pH 5.0 to 8.0, respectively. The CGTase was relatively stable after heating at 550C for 10 minutes, and maintained its activity at the pH 5.0 to 9.0. The enzyme activity was inhibited by the presence of 1 mM metal ions and cause CGTase lost approximately 40% of its activity. Among the metal ions it was found that Cu2+ was the strongest inhibitor, with presence of 1mM Cu2+ the residual activity of CGTase was 24.4%. Results of purification showed that Specific activities of the enzyme during purification were 269 U/mg (crude enzyme); 955 U/mg (dialysis); 481 U/mg (gel fitrations); and 544 U/mg (ion exchange chromatography).